2012
DOI: 10.1029/2010wr010100
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of hydrologic trends from a water balance perspective: The role of groundwater storage in the Budyko hypothesis

Abstract: [1] We investigate the observed positive trends in annual runoff in several basins in central Nebraska using the Budyko hypothesis as a diagnostic tool. In basins where runoff is dominated by base flow we found that the estimated annual evapotranspiration (ET a ) to precipitation (P) ratio (ET a /P) from data is negatively related to the aridity index (ET p /P, where ET p is potential annual evapotranspiration). This observation is inconsistent with the Budyko hypothesis. We hypothesized that the observed nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 67 publications
(98 reference statements)
6
124
0
Order By: Relevance
“…Recently, the BH has been widely used to investigate the interannual variability of precipitation partitioning (Gerrits et al, 2009), separation of runoff trends (H.-Y. Xiong et al, 2015), evapotranspiration change (Savenije, 1997) and water storage change (Istanbulluoglu et al, 2012;Gao et al, 2014). These studies show that hydrological processes have been greatly affected by the climate change and intensive change of land cover owing to human activities.…”
Section: Du Et Al: Role Of Water Balance In An Extended Budyko Hymentioning
confidence: 99%
“…Recently, the BH has been widely used to investigate the interannual variability of precipitation partitioning (Gerrits et al, 2009), separation of runoff trends (H.-Y. Xiong et al, 2015), evapotranspiration change (Savenije, 1997) and water storage change (Istanbulluoglu et al, 2012;Gao et al, 2014). These studies show that hydrological processes have been greatly affected by the climate change and intensive change of land cover owing to human activities.…”
Section: Du Et Al: Role Of Water Balance In An Extended Budyko Hymentioning
confidence: 99%
“…However, poor performance in some locations, especially over annual or seasonal time periods, has been attributed to the influence of storage changes that violate the steady-state assumption (Milly and Dunne, 2002;Zhang et al, 2008). Istanbulluoglu et al (2012) and Wang et al (2009) showed interannual storage changes can produce a negative correlation between the evapotranspiration ratio and aridity that is counter to the Budyko curve for baseflowdominated basins in the Nebraska Sand Hills. Wang (2012) evaluated inter-annual storage changes for twelve watersheds in Illinois and showed that, on an annual timescale, variability in runoff and storage is larger than evapotranspiration, and accounting for storage can improve the performance of Budyko predictions.…”
Section: E Condon and R M Maxwell: Systematic Shifts In Budyko mentioning
confidence: 99%
“…Most of these studies have been applied at single basins (Donohue et al, 2011;Jiang et al, 2015;Liang and Liu, 2014;Liu and McVicar, 2012;Roderick and Farquhar, 2011;Xu et al, 2014;Zhang X. et al, 2014) or multiple basins within a single region: USA (Chen et al, 2013;Wang and Hejazi, 2011;Carmona et al, 2014;Istanbulluoglu et al, 2012), Australia (Donohue et al, 2010(Donohue et al, , 2012Teng et al, 2012), China (Yang D. et al, 2007(Yang D. et al, , 2009Yang and Yang, 2011;Yang H. et al, 2014;Cong et al, 2015;Xiong and Guo, 2012;Yu et al, 2013) and Europe (Velde et al, 2014;Oudin et al, 2008). The global scale studies have also been conducted but mainly focusing on the development of the Budyko functional forms (Koster and Suarez, 1999;Zhang L. et al, 2001;Arora, 2002) and their parameters (Li et al, 2013;Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%